In silico screening oil compounds of Nigella sativa L. as potential SARS-CoV-2 Omicron spike protein inhibitors - Nadia Riqqah Nurlayla; Valenski Sicilia; Ananda Kautsar Nadia Faya; Michelle Fai; Peta Aurora Aga; Elsa Rahmania Criswahyudianti; Fatchiyah Fatchiyah (JSMARTech, 2022)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), has led to a global pandemic. Hence, identifying prospective inhibitors of spike protein SARS-CoV-2 drugs is urgently required for combatting SARS-CoV-2 entry by binding to human angiotensin-converting enzyme 2 (ACE-2). This study evaluated five Nigella sativa L. essential oil compounds as potential SARS-CoV-2 Omicron spike protein inhibitors. Its essential oil has a long history of traditional useas a natural treatment for numerous ailments and disorders. Five compounds of N. sativa essential oil, including thymoquinone, p-Cymene, dithymoquinone, thymohydroquinone, thymol, and bisoxatin as control, were downloaded from the PubChem database. The 3D structure of ACE-2 and spike proteins of the SARS-CoV-2 Omicron variant were retrieved from Protein Data Bank RCSB. The compounds and proteins were prepared by PyRx 0.8 version and Discovery Studio ver 21.1.1, then docked with Hex 8.0.0 and analyzed using Discovery Studio ver 21.1.1 and LigPlot+. According to Lipinski's five rules and Veber's rules, all compounds showed drug-likeness. ADMET evaluation implied five compounds of N. sativa essential oil are well absorbed with consideration of its potential hepatotoxicity. Molecular interactions showed that all compounds, including bisoxatin, have a higher affinity for the ACE-2 protein by thymohydroquinone and thymol are more likely to bind with ACE 2 as the binding energy is higher than control. Therefore, N. sativa L. essential oil compounds are potent to be the inhibitor of SARS-CoV-2 infections by blocking the binding of the spike protein to ACE-2.